Internal carotid artery stenosis: hemodynamics in the ipsilateral ACA affects CT angiography manifestations - Li, Chun; Meng, Jihong; Xu, Baoxin; Li, Xiaodong; Li, Miaomiao; Du, Xue; Li, Shaoyi; Ma, Weining (Frontiers in Neuroscience, 2023)
Objective This study aimed to evaluate whether CT angiography (CTA) manifestations in anterior cerebral artery a1 segment (A1) were related to the hemodynamics in patients with internal carotid artery stenosis (ICAS). Methods A total of 97 cases were selected. The degree of ICAS and symmetry of A1 were evaluated by CTA examination. Hemodynamic indexes were detected by transcranial Doppler (TCD). The differences in CTA presentations of A1 and hemodynamics between the vessels on the stenotic and contralateral sides were analyzed according to the different degrees of stenosis. The degree of ICAS according to the different manifestations of A1 and the hemodynamics of A1’s adjacent vessels were also analyzed. Results In the case of unilateral ICAS, the difference in Vm of A1 between the stenotic and the contralateral side was the most significant relative to the stenosis degree. When unilateral ICAS was≥70%, the presentation of A1 on the stenotic side was more slender or non-visualized compared to that on the contralateral side, while in cases with unilateral stenosis <70% or bilateral stenosis with a similar degree of stenosis, A1 were mainly symmetrical. When A1 on the side of ICAS was slender or non-visualized, the Vm of A1 was significantly slower than that on the contralateral side (P<0.001). Conclusion The CTA manifestations of A1 on the side of ICAS embodied the overall changes of the intracranial hemodynamics after ICAS. A combination of TCD and CTA examination of A1 can assist in judging the location and degree of ICAS.